Market research of an articular analysis instrument: a practical case - Tortosa Tarancón, A. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2019)
The launch of new products process must be based on market data that let make an entrance and communication strategy that will make decrease uncertainty. The main objective of this market research is to establish a suitable sales and communication strategy for an ankle analysis instrument. To reach the objective, a questionnaire was administered to 138 athletes and 130 physiotherapist. The results support a communication strategy based in a push model and a focused sales model, without necessity of segmentation by pay availability or age. We can conclude that this market research had the result expected, and helped to the creation of the right marketing strategies focused on the product-market fit.